The correlation between the service sector and gross domestic product in Brazil (Research, Society and Development, 2020)
In recent years, the services sector has presented itself as a very important variable in the composition of gross domestic product (GDP), thus collaborating in the generation of jobs and income, as well as contributing to the development of the country's economy. Following this line of reasoning, this paper aims to analyze the correlation between the service sector and GDP in Brazil, in the period 2000 - 2017. The study is based on the approach that deals with GDP from the perspective of supply (production). The methodological use is based on the interpretation of gdp and current gross value added from the service sector; thus, the collected data are secondary, for analysis and tabulation was used Excel and Stata software to extract its modeling. When observing the behavior of the variables studied, it is noted that an increase in GDP causes an increase in services, in addition, by adding a unit in income its effect is increasing, making one understand the importance of the service sector in the daily life of individuals and the national economy. Thus, it was concluded that there is a positive correlation between the variables selected for the analysis, thus, the increase in income (GDP) causes an increase in Brazilian services.